UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI STRATEGI PEMBELAJARAN TIME TOKEN PADA MATA PELAJARAN PPKN DI SMA NEGERI 1 TOMA TAHUN PELAJARAN 2022/2023 - Darwin Gaurifa (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to determine the increase in student learning outcomes through the application of the Time token learning strategy in PPKn class XI SMA Negeri 1 Toma. The research method used is a qualitative research method with the type of research is Classroom Action Research (CAR). The subjects of this study were class XI students of SMA Negeri 1 Toma in the 2022/2023 academic year. XI class research objects with a total of 36 people. Research findings using the Time token learning strategy show that the results of processing learning outcomes in cycle I were obtained at 52.77% while processing learning outcomes in cycle II was 86.11%. So it can be concluded that the Time token learning strategy is a more effective learning strategy to improve student learning outcomes. Because the Time token learning strategy makes students more active in the teaching and learning process. Suggestions offered by researchers, the Time token learning strategy should be used as an alternative in learning because it can improve student learning outcomes more actively and effectively.